76-2x=13-9x

Simple and best practice solution for 76-2x=13-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 76-2x=13-9x equation:


76-2x=13-9x

We simplify the equation to the form, which is simple to understand
76-2x=13-9x

We move all terms containing x to the left and all other terms to the right.
-2x+9x=+13-76

We simplify left and right side of the equation.
+7x=-63

We divide both sides of the equation by 7 to get x.
x=-9

See similar equations:

| 10y-50=-150 | | x-3y=29 | | 50x^2=98 | | 5/9n-2=2/3n | | -14=-7x+2(6x-22) | | 2x=6.8 | | 7(6-3x)+2= | | 72=4.5n | | -4v-2v-16=38 | | lnx+ln(x+5)=ln(8x+10) | | -x-42=-3x+14 | | 5(-x+7)=20 | | 10-5(9n-9)=10-5 | | 6y-2=-3 | | 20y^2+9y-20=0 | | 04(1.5c+6)-2c=-9 | | x-20=60 | | 3x+6y+4z=2900 | | 7x-11=3x-3 | | 140=192-w | | -3x+6(2x+9)=9 | | 5x-34=17 | | x+10=400 | | 2x+3x+15=30 | | 3+2n= | | 125=-w+236 | | -2r+6(r-1)+3r-(4-r)=(r+5)-5 | | 4-7j=f-12 | | 1+1=8 | | -v+61=185 | | (7t-2)(-3t+1)=-3(1-3t) | | 22-6=4h |

Equations solver categories